Locality and Implementation of Human Rights City - Lia Nihlah Najwah; Arief Setiawan (Faculty of Social and Political Sciences, Universitas Diponegoro, 2021)
This article originated from studies that posed questions on the influence of Wonosobo for Human Rights Friendly City implementation in relation to religious tolerance in Buntu Village, Kejajar District. The study aims to identify the impact of the Human Rights Friendly City status that Wonosobo bears on the increasing religious tolerance in Buntu Village. Religious tolerance, which serves as one of Wonosobo's focuses on the Human Rights City agenda, becomes the limitation of this study. The time frame of this research ranges from 2016-2020, especially after the promulgation of Regional Government of Kabupaten Wonosobo Regulation Number 5 of 2016 concerning Wonosobo Regency for Human Rights Friendly City. This study uses a qualitative approach as its research method while utilizing interviews and literature studies as its data collection methods. It is worth noting that Buntu Village already possessed religious diversity and a high level of tolerance in its society even before the Human Right Friendly City policy was ratified as one of Wonosobo’s priorities. However, this study finds that tolerance in Buntu Village runs naturally without any external intervention. The Human Rights Friendly City status plays a tiny role in improving the quality of tolerance in Buntu Village. Hence, our study suggests that it is necessary for the regional government to increase the level of seriousness to continuously implement the program in the form of budget politics or other development programs.